2014
DOI: 10.1002/adfm.201401547
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Processing Additives Tune the Nanoscale Morphology of High Efficiency Organic Photovoltaic Blends: From Casting Solution to Spun‐Cast Thin Film

Abstract: Adding a small amount of a processing additive to the casting solution of photoactive organic blends has been demonstrated to be an effective method for achieving improved power conversion effi ciency (PCE) in organic photovoltaics (OPVs). However, an understanding of the nano-structural evolution occurring in the transformation from casting solution to thin photoactive fi lms is still lacking. In this report, the effects of the processing additive diiodooctane (DIO) on the morphology of the established blend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 36 publications
1
45
2
Order By: Relevance
“…Researchers have shifted model materials for morphological understanding from PTB7 to other high-effi ciency PBDTTT polymers such as PBDTTT-C-T [ 36,55,56 ] and PTB7-Th. [ 57,58 ] For instance, Xiao et al [ 55 ] used a comprehensive set of characterization techniques including small-angle neutron/X-ray scattering and neutron refl ectometry to reveal the impact of DIO on the PBDTTT-C-T:PC 71 BM morphology from the cast solution to the solid fi lm; they found that DIO is critical for enhancing wileyonlinelibrary.com crystallinity and strongly improving both lateral and vertical phase segregation in the fi lm solidifi cation stage (see Figure 5 ).…”
Section: Understanding Of the Morphology Of Opvs Featuring Well-knownmentioning
confidence: 99%
“…Researchers have shifted model materials for morphological understanding from PTB7 to other high-effi ciency PBDTTT polymers such as PBDTTT-C-T [ 36,55,56 ] and PTB7-Th. [ 57,58 ] For instance, Xiao et al [ 55 ] used a comprehensive set of characterization techniques including small-angle neutron/X-ray scattering and neutron refl ectometry to reveal the impact of DIO on the PBDTTT-C-T:PC 71 BM morphology from the cast solution to the solid fi lm; they found that DIO is critical for enhancing wileyonlinelibrary.com crystallinity and strongly improving both lateral and vertical phase segregation in the fi lm solidifi cation stage (see Figure 5 ).…”
Section: Understanding Of the Morphology Of Opvs Featuring Well-knownmentioning
confidence: 99%
“…Nanomorphology plays a crucial role in BHJ solar cells as it dictates both charge generation and transport [5][6][7]. Nanomorphological features such as donor/acceptor crystallinity [8], vertical/ lateral phase separation [9,10], domain purity [11], orientation [12] and domain interfaces [13] can be tailored by optimizing the processing conditions to enhance device conversion efficiencies. Processing parameters such as solvent selection [8,14,15], annealing temperature [16], donor-acceptor mixing ratio [17,18], and coating techniques can be fine-tuned to attain high photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al [19] also found that the DIO additives could significantly facilitate the molecular ordering in the spin-coated films. Two-dimensional (2D) grazing- [19].…”
Section: Processing Additivesmentioning
confidence: 95%
“…The opposite structural evolution upon adding additive is determined by distinctive initial states without additives processing, which is related with the intrinsic factors of solubility, crystallization ability, and miscibility between BHJ components. Shao et al [19] observed that both lateral and vertical morphology of the PBDTTT-C-T:PC 71 BM blend films could be optimized by using a small amount of additive of 3 % DIO. Low-voltage energy filter transmission electron microscopy (EF-TEM) was applied to reveal the phase and morphology in PBDTTT-C-T: PC 71 BM blend films with DIO and without DIO.…”
Section: Processing Additivesmentioning
confidence: 99%
See 1 more Smart Citation